A study of clinicopathological profile and treatment outcomes in patients with autoimmune hemolytic anaemia - I., Lavanya Sri; M., Jagadeesan; P., Nithyananthan; S., Prasanna Karthik; R., Kannan; K., Rajendran; S., Magesh Kumar (International Journal of Advances in Medicine, 2019)
Background: Autoimmune haemolytic anaemia (AIHA) is relatively uncommon condition with grave consequences, if not diagnosed and treated early. The literature on the clinical outcome and response to treatment is relatively scarce. Aim was to study the clinic-pathological profile and the treatment outcomes in patients with AIHA. Methods: Around 25 patients with AIHA attending a tertiary care hospital over a period of one year were included in the study. The patients were divided based on severity of anaemia and etiology. All the patients data were analysed for the demographic data, clinico -pathological findings and the response to treatment. All the patients data were analysed using SPSS software (version 22). Results: Out of 25 patients, 76% were females and 24% were males. Based on severity of anaemia, 60%, 28% and 8% had severe, moderate and mild anaemia. Around 48% of the patients had thrombocytopenia along with anaemia. 8 (32%) and 17 (68%) patients have primary and secondary AIHAs respectively. In our study the commonest cause for the secondary AIHA was Systemic Lupus Erythematosus (SLE) followed by haematological malignancy, primary Sjogrens, Anti-phospholipid antibody (APLA) syndrome, carcinoma colon and Wilsons disease. Hepatosplenomegaly and lymphadenopathy were present in 36% and 4% respectively. Out of 22 (88%) patients on corticosteroid therapy, 15 (60%) patients responded to corticosteroids alone and 6(24%) patients required corticosteroid plus immunosuppressive therapy. Conclusions: AIHA has to be ruled out in all anaemia patients with indirect hyperbilirubinemia and abnormal peripheral smear. Secondary AIHA is more common than primary. Corticosteroids and immunosuppressive agents are the mainstay of treatment of AIHA.